Keterlibatan Asean dalam Menangani Konflik Myanmar (Studi Kasus: Konflik Etnis Rohingya 2017 â€“ 2019) - Setiawan , Ipung Pramudya; Suryanti, Made Selly Dwi (Politicos: Jurnal Politik Dan Pemerintahan, 2021)
This paper will study about ASEANâ€™s role on the conflict in Myanmar, specifically Rohingya ethnical conflicts in 2017-2019. In its development, this conflict turns out to be far from over and ASEAN as the regional organization of South-East Asia should take the responsibility to solve this conflict. This paper will be reviewed using descriptive qualitative approach that is based on secondary data sources. Those data sources include academic journals, books, printed and online articles, and also other relevant sources. We concluded that the involvement of ASEAN in solving the conflict in Rohingya was because the responsibility of ASEAN to protect the countries in their region. In the effort to solve the conflict of Rohingya, ASEAN never wandered off the human rights principles. Meanwhile, in the process, ASEAN was assisted by Indonesia to approach it through soft diplomacy and by the United Nations (UN) through the concept of â€œResponsibility to Protectâ€. On the other hand, ASEAN also have a special team called ASEAN HUMANITARIAN ASSISTANCE (AHA). This team was specifically assigned in Rakhine and making 4 (four) recommendations according physical security, materials security, Rohingya registration, and social unification to prevent the recurrence of horizontal conflict in Myanmar.